Madame Bovary - Courcel, Nicole; Bouise, Jean; Dussollier, André; Cardinal, Pierre, 1924-; Flaubert, Gustave, 1821-1880 (Films for the Humanities, 1986)
A story about a woman who rebels at the provincial life forced upon her and engages in a series of illicit affairs.